From the "Unworthy" to the "Benevolent": How King Zhao "Knew the Great Way" - Wen, Jinxin (Journal of Theory and Practice of Social Science, 2024)
For King Zhao of Chu, he was regarded as a "do‐nothing" ruler in the first period of his reign, but with the end of the Wu Ren Ru Ying, he was regarded as a "benevolent ruler" who could lead the Chu state to prosperity. In the process of this change of concept, Confucius, who thought that "I am a man who destroys and acclaim, but if he has an accolade, he has a proof", once praised King Zhao of Chu and called him "a man who knows the Great Way". Therefore, this paper will discuss three aspects of King Zhao's ruling behavior, namely, governance, virtue and attitude towards providence, based on the records in the unearthed documents, in order to discuss why King Zhaoge was praised by Confucius as "knowing the Great Way". This study focuses on the third volume of The Governance of China and its English rendition, utilizing a bilingual parallel database to summarize the classification of Chinese idioms in the book and their corresponding translation methods. The translation of these idioms is analyzed from three fundamental dimensions of ecotranslatology theory: linguistic, cultural, and communicative. It is suggested that when translating Chinese idioms in political texts, translators need to apprehend the fundamental semantics and cultural connotations embedded within them. Concurrently, it is essential that they tailor their approach to resonate with the expectations of the readership of the target language. This necessitates the judicious application of a spectrum of translation strategies - inclusive but not limited to literal, free, and combined translation - to accommodate the linguistic, cultural, and communicative ecological environments of the target language. By adopting this methodology, the translation aims to present, to the greatest extent, the grandeur of a great nation nurtured by excellent traditional Chinese culture to the international community.